Судовий конституційний контроль за додержанням процедури внесення змін до Конституції України - Шевчук, Ірина Миколаївна; Shevchuk, I. M. (Ужгородський національний університет, 2012)
У статті досліджено діяльність Конституційного Суду України, як органу судового конституційного контролю за додержанням процедури внесення змін до Конституції України. Обгрунтовано необхідність наступного судового конституційного контролю щодо закону про внесення змін до Конституції України. Визначено правову природу законів про внесення змін до Конституції України.The article deals with the activity of the Constitutional Court of Ukraine as the body of constitutional control over the Constitution of Ukraine alteration procedure. Theneed for the further judicial review of constitutionality as to the Law of the Constitution of Ukraine alteration is demonstrated. The legal nature of the laws of the Constitution of Ukraine alteration is determined.
The constitutional control over the constitution of Ukraine alteration procedure
Keywords: Конституція України; порядок внесення змін до Конституції України; Конституційний Суд України; судовий конституційний контроль; конституційні закони; the Constitution of Ukraine; the order of the Constitution of Ukraine alteration; the Constitutional Court of Ukraine; the judicial review of constitutionality; constitutional laws